The Impact of Oil Prices on Income in Azerbaijan - Humbatova, Sugra Ingilab; Hajiyev, Natig Gadim-Ogli (International Journal of Energy Economics and Policy, 2022)
Oil prices in the global market have been fluctuating sharply since the end of the XX century. As oil is a predominant component that affects global indicators, it is necessary to assess by economists. Because GDP per capita, exchange rate, and total trade turnover depend on the effects of oil price shocks. This article researched the impact oil fluctuations on income from a short and long-term perspective. For the purpose of the research, Azerbaijan has been exemplified as an oil-producing country for the period of 2001m01-2021m06. Applying the empirical method, we achieved that world oil shocks affected income (in dollar) significantly in a short perspective. The recent declining oil prices make this topic more valuable to research. Moreover, as many empirical methods show asymmetric dependency, the research focused mainly on negative shocks of oil prices.